Nonlinear Effects of Taxation on Growth - Jaimovich, Nir; Rebelo, Sergio (Journal of Political Economy, 2017)
We propose a model consistent with two observations. First, the tax rates adopted by different countries are generally uncorrelated with their growth performance. Second, countries that drastically reduce private incentives to invest severely hurt their growth performance. In our model, the effects of taxation on growth are highly nonlinear. Low tax rates have a very small impact on long-run growth rates. But as tax rates rise, their negative impact on growth rises dramatically. The median voter chooses tax rates that have a small impact on growth prospects, making the relation between tax rates and economic growth difficult to measure empirically.